Answer:
The answer is below
Explanation:
Given that f(x) = x√3.
A function can be vertically stretched or compressed by multiplying it by a positive constant. If the constant is greater than 1, it is vertically stretched and if the constant is less than 1 it is vertically compressed.
If a function f(x) = x is compressed or stretched by a constant a, then the new function g(x) = a f(x)
If a function f(x) = x is translated a units down, then the new function g(x) = f(x) - a
If a function f(x) = x is translated a units left, then the new function g(x) = f(x-a)
If f(x) = x√3 is compressed vertically by a factor of 1/3. The new function is
[tex]f(x)'=x\sqrt{3} *\frac{1}{3} \\\\f(x)'=\frac{x}{3} \sqrt{3}[/tex]
If it is then translated 3 units left and 7 units down, the transformed function g(x) is:
[tex]g(x)=(\frac{x-3}{3}\sqrt{3} )-7[/tex]